TECHNIQUE IN TEACHING GRAMMAR FOR THE FIRST GRADE OF JUNIOR HIGH SCHOOL STUDENT THROUGH GAMES - Muhammad Wahyu Widiyanto; Maria Yustina Rensi Dartani; Indri Kustantina (ETERNAL (English Teaching Journal), 2012)
The purpose of this study is to find out the contribution of games in improving grammar acquisition of the Yoannes Junior High School students. In teaching Grammar, teachers should apply the appropriate technique and method. In this study, games are chosen to be used.  Participants are divided into treatment group, the experimental group and the control group. The experimental group is taught by using games and the control group is taught by using the memorizing method. Each group is assigned to do the same test, containing sections which involved grammar items. They attended the course, once a week for eight weeks. Each meeting lasted forty five minutes. The material is taken from textbook that applied at school. Pre- test is given before the experiment and post- test is held immediately after the experiment is over. The Null hypothesis of no significant differences are constructed and tested, and then one- tailed T- test is used to compare the score of the games and memorizing groups and to analyze the hypothesis. The alpha level is set. Teaching the arbitrary rules of grammar to students who cannot speak, understand of use the English language is an absolute waste of time, effort and money and is downright foolish. The practice is about as rational as teaching advanced race car skid control to someone who does not know how to drive. In English conversation, get them talking, get them comfortable using the language, then teach them by using rules of grammar once they understand the language.